Actuarial Modeling of COVID-19 Insurance - Mila Kurniawaty; Maulana Muhamad Arifin; Bagus Kurniawan; Sadam Laksamana Sukarno; Muhammad Teguh Prayoga (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
In this article, we provide an actuarial model expected to be able to help financial arrangements to cover losses due to the outbreak of coronavirus disease (COVID-19). We construct the dynamical models of premium and benefit based on generalized SEIR (Susceptible-Exposed-Infected-Recovered). Based on its dynamical model, we formulate the premium and the premium reserves on hospitalization and death benefits of the COVID-19 insurance.